Facile synthesis of efficient visible active C-doped TiO2 nanomaterials with high surface area for the simultaneous removal of phenol and Cr(VI). (January 2015) - Mani, A.Daya; Reddy, P.Manoj Kumar; Srinivaas, M.; Ghosal, P.; Xanthopoulos, N.; Subrahmanyam, Ch.
Graphical abstract: Highlights: Facile synthesis of C-doped TiO2 nanomaterials with high surface area. Utilization of citric acid and ascorbic acid as fuels based on evolution of gases. Enhanced visible activity for the oxidation of phenol and reduction of Cr(VI). Study of simultaneous oxidation of phenol and reduction of Cr(VI) for the first time. Proposed plausible mechanism for the simultaneous removal of phenol and Cr(VI). Abstract: A single step synthesis of carbon doped TiO2 (anatase) nanomaterials have been reported by using combustion synthesis using ascorbic acid and citric acid fuels. X-ray diffraction studies indicated the formation of nanosized anatase titania, whereas, transmission electron microscopy confirmed the formation of nanosized TiO2 anatase. The carbon doping into TiO2 matrix was identified by X-ray photoelectron spectroscopy, whereas, thermogravimetric study quantified the carbon doping. Diffuse reflectance UV–vis spectra indicated the band gap of less than 3 eV, a prerequisite for the photocatalytic activity under visible light irradiation. The N2 adsorption studies revealed the high surface area (upto 290 m 2 /g) of the synthesized photocatalysts. Typical photocatalytic activity data indicated that the simultaneous removal of Cr(VI) and phenol is advantageous than degradation of the individual pollutants.